THE IMPLEMENTATION OF CONSTRUCTIVISM IN WRITING ANALYTICAL EXPOSITION TEXT - Feriyanti, Dessy; Apriliaswati, Rahayu; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This study was a classroom action research (CAR) to improve students’ writing ability on analytical exposition text in senior high school students. In this study, constructivism was implemented as a strategy to help student in writing analytical exposition. Constructivism consists of orientation, elicitation, restructuring idea, application of idea and review. The techniques of data collecting in this research were observation and written test. Data was analyzed by using scoring profile. The students’ writing ability in analytical exposition text improved in two cycles from 75.55 in cycle 1 then improved to 82.40 in cycle two. The improvements of this study were particularly in students’ writing on generic structure, and mechanics. Keywords: writing, analytical exposition text, constructivism.   Abstrak: Penelitian ini adalah penelitian tindakan kelas (CAR) yang bertujuan unuk meningkatkan kemampuan siswa dalam menulis sebuah teks analytical exposition pada siswa sekolah menengah atas. Dalam penelitian ini, constuctivism diimplementasikan sebagai sebuah strategi untuk membantu siswa dalam menulis teks analytical exposition. Teknik pengumpulan data yang digunakan meliputi observasi dan tes tertulis. Hasil data penelitian dianalisi menggunakan rubrik penilaian. Kemampuan siswa dalam menulis teks analytical exposition mengalami peningkatan dalam pada dua siklus dari 75.55 pada siklus pertama kemudian meningkat menjadi 82.40 pada siklus kedua. Peningkatan yang dialami siswa pada penelitian ini umumnya terjadi pada penulisan struktur generik dan mekanisme penulisan teks analytical exposition. Kata Kunci: menulis, teks analytical exposition, constructivism